PENGARUH SOSIALISASI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Meliana Anggraini; Siti Asmonah (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This study aims to 1) determine the effect of tax socialization on motor vehicle taxpayer compliance at the Cinere SAMSAT Office 2) to determine the effect of taxpayer awareness on motor vehicle taxpayer compliance at Cinere SAMSAT Office 3) to determine the effect of tax socialization and taxpayer awareness simultaneously on motor vehicle taxpayer compliance at the Cinere SAMSAT Office. The background of this study is based on the importance of Motor Vehicle Tax (PKB) revenue as one of the main sources of Regional Original Income (PAD). The low level of compliance is seen from the large number of Vehicles Not Re-Registed (KTMDU) and the increasing number of fines. The method used quantitative with an associative approach. Primary data was obtained by distributing questionnaires to 100 respondents who are motor vehicle taxpayers at the Cinere SAMSAT Office. The analysis technique used is multiple linear regression with SPSS version 30 and Microsoft Excel software tools. The partial result of the study indicate that 1) the tax socialization variable has a positive and significant effect on motor vehicle taxpayer compliance, with a calculated t-value of 7,574 > t-table of 1,98472 an a significant value of <,001 2) the taxpayer awareness variable also has a positive and significant effect on motor vehicle taxpayer compliance, with a calculated t-value of 8,461 > t-table of 1,98472 and a significant value of <,001. Meanwhile, the simultaneous analysis shows that tax socialization and taxpayer awareness simultaneously have a posiitve and significant effect on motor vehicle taxpayer compliance at the Cinere SAMSAT Office, with a calculated f-value of 36,988 > f-table of 3,09 and significance value of <,001. Keywords: Tax Socialization, Taxpayer Awareness, Motor Vehicle Taxpayer Compliance.